2022
DOI: 10.1007/s13313-022-00879-4
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide control of Gnomoniopsis smithogilvyi, causal agent of chestnut rot in Australia

Abstract: Chestnut rot caused by Gnomoniopsis smithogilvyi is considered a severe threat to the production of chestnuts from European chestnut (Castanea sativa Mill.) in Australia and overseas. Currently, most of the control strategies are applied post-harvest and little is known about the use of fungicides to reduce nut infection in orchards early in the season. This research evaluated the effectiveness of various fungicides against the pathogen in vitro and selected the most effective products for field trials. In vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…Moreover, those were described as showing cross-resistance even for fungicides with a different mode of action , which might be the reason for their high sequence read abundances in the insecticide Steward ® -treated bees (Figure 4A). Similar to the cuticular fungal community composition, the diversity of functional composition was increased due to the fungicide Difcor ® , insecticide Steward ® , and PPP mix A treatments, which were already observed for the intestinal microbiome of bees (Silva-Campos et al, 2022).…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, those were described as showing cross-resistance even for fungicides with a different mode of action , which might be the reason for their high sequence read abundances in the insecticide Steward ® -treated bees (Figure 4A). Similar to the cuticular fungal community composition, the diversity of functional composition was increased due to the fungicide Difcor ® , insecticide Steward ® , and PPP mix A treatments, which were already observed for the intestinal microbiome of bees (Silva-Campos et al, 2022).…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, those were described as showing cross-resistance even for fungicides with a different mode of action (Yang et al, 2019), which might be the reason for their high sequence read abundances in the insecticide Steward ® -treated bees (Figure 4A). Similar to the cuticular fungal community composition, the diversity of functional composition was increased due to the fungicide Difcor ® , insecticide Steward ® , and PPP mix A treatments, which were already observed for the intestinal microbiome of bees (Silva-Campos et al, 2022).…”
Section: Discussionsupporting
confidence: 56%
“…Similarly, the fungicide Difcor® significantly reduced the fungal gene copy numbers ( Supplementary Figure 1B ), and members of the genus Amphiporthe were significantly associated with this treatment. However, a recent study found that members of the same family, Valsaceae, were described as sensitive toward difenoconazole ( Silva-Campos et al, 2022 ), indicating an ambivalent biocide response in this family. Furthermore, Steward® significantly changed cuticular fungal community composition and function ( Figures 3B , 4A ; Supplementary Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, growers would have timely information that would enable them to design and implement effective control strategies for chestnut rot. For example, in our recent report on the use of fungicides to control G. smithogilvyi in the field [18], we used this mPCR technique, across a growing season, to monitor the level of nut infection after fungicide applications.…”
Section: Discussionmentioning
confidence: 99%
“…Implementing control strategies, such as the use of fungicides [18], for plant diseases is time-dependent and relies on the detection and identification of the causative agent precisely and rapidly [19,20]. Currently, numerous plant pathogens, including ascomycetes [21], basidiomycetes [22,23] and oomycetes [24], are detected quickly and accurately using PCR-based techniques [25].…”
Section: Introductionmentioning
confidence: 99%